Arcite's Consolation: Boethian Argumentation and the Phenomenology of Drunkenness. (2nd January 2016) - Yu, Wesley Chihyung
Abstract : In Chaucer's Knight's Tale, Arcite's metaphor of a "dronke man" triggers an investigation of validity and its changing definition through the Middle Ages. By reading this metaphor through the medieval history of probable argumentation, this article expands upon philosophical preoccupations embedded in Chaucer's "dronke man." Deriving from Boethius' illustration of the ebrius, where it appears as a lesson in Boethian argumentation, poetic drunkenness can express an emergent epistemology outside of the parameters of a historically pervasive neoplatonism. In this way, Chaucer's understanding of high philosophy is anchored to an argumentative foundation outlined by the curriculum of early logic, with which rhetoric and poetics share a curious lineage.